Computers in Cardiology 2001. Vol.28 (Cat. No.01CH37287)
DOI: 10.1109/cic.2001.977703
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac aliasing in atrial rate variation response to fixed-rate ventricular pacing

Abstract: It is found that the frequency components of atrial rate variation (ARV) of A V-block patient with fixed-rate ventricular pacing valy irregularly with the pacing rates.We attempt to learn about the relationship between the oscillation frequency of AR V and the blood pressure (BP) pattern in this study.The beat-to-beat AR Vs extracted from esophageal ECG and noninvasive BP waveforms of seven AV-block patients were recorded. Each patient was paced under 60, 90, 120 beatdmin of three ventricular rates. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The lead II surface ECG and NICBP were simultaneously recorded and sampled at 500 Hz for further processing. The experimental procedure was described in previous work [9].…”
Section: Data Acquisitionmentioning
confidence: 99%
“…The lead II surface ECG and NICBP were simultaneously recorded and sampled at 500 Hz for further processing. The experimental procedure was described in previous work [9].…”
Section: Data Acquisitionmentioning
confidence: 99%
“…It is found that the dominant frequency of ARV is an aliasing of ventricular pacing rate while considering the mean atrial rate as the sampling rate [6]. It is suggested that the BP pulse rate and waveform play an important role for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies was reported that ventricular rate and AV-delay have marked influences on ARV [2,3] Moreover, some evidences have shown that beat-to-beat blood pressure (BP) variation (BPV) may play a role for this phenomenon [4,5]. In our later investigation [6], we found that the oscillation frequency of ARV may be an aliasing phenomenon of BP pulse frequency exactly equal to ventricular rate when the mean atrial rate is considered as the sample rate of ARV signal. Hence we suggested that the BP pulse dominate the ARV in AV dissociation situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation